社會性科學議題決策學習模組的成效 Effects of a SSI-Based Learning Module on Students' Decision-Making Abilities - 張文馨 Wen-Xin Zhang; 許瑛玿 Ying-Shao Hsu; 何玉婷 Yu-Ting Ho; 劉承珏 Cheng-Chueh Liu (National Taiwan Normal University, 2023)
本研究旨在發展一個有效的社會性科學議題決策學習模組來提升學生在這類複雜議題中的決策能力，並探討此模組對學生決策能力之影響。模組以氣候變遷調適為議題主軸，依據四大要素進行規劃：一、提供具體的決策架構；二、提供訓練活動，提升學生對決策策略的認識；三、提供小組協作機會；四、提供反思機會，並於數位平台上建置引導流程，由教師帶領學生逐步解讀資料及進行決策。本研究採單組前、後測設計，以便利取樣方式邀請一位在職教師在其五個授課班級實施學習模組，共172位來自臺北市某高中女校的學生參與研究。研究資料來自學生的前測、學習模組中、後測的填答內容，將填答內容進行編碼計分後，再透過描述性統計、相依t檢定等分析方式，探討學生在學習模組前、中、後的決策能力。結果指出，本研究發展的學習模組顯著提升學生的決策能力，包含議題的多元面向的思考、決策方法的使用、反思並評估自身決策的精確性。此結果顯示，研究中所使用的學習模組在辨識議題階段、差異化階段及鞏固決策階段皆具有不同特性，可以提升學生的決策能力。不過， 模組雖能協助學生瞭解使用補償性方法做決策的重要性，但部分學生對正確使用這些補償性方法有錯誤理解，例如在使用補償性方法時採計錯誤的判準，抑或無法針對不同面向的判準進行正確的權重，甚至與刪去法混淆，顯示補償性方法的理解對學生來說仍較困難。 Research Motivation and Purpose The Curriculum Guidelines of 12-Year Basic Education in Taiwan emphasize the cultivation of students' core literacy and encourage teachers to design and implement cross-disciplinary courses in an issue-oriented manner (National Institute of Education, 2014). Core competency is defined as "all information, ability, and attitude that a person should possess to equip him or her for daily life and for tackling future challenges" (National Institute of Education, 2014). Accordingly, social science issues (SSIs) can be a suitable approach for curriculum design to cultivate students' core competencies. An SSI curriculum enables students to obtain knowledge across different disciplines; resolve dilemmas with others in a critical but respectful manner; and develop higher-order thinking skills such as argumentation, reasoning, and decision-making (Zohar & Nemet, 2002). These goals correspond to that of the new Curriculum Guidelines of 12-Year Basic Education in Taiwan, which is to cultivate the ability to solve real problems among students. Although studies have confirmed that SSI-based teaching can improve students' understanding of scientific concepts and enhance their higher-order thinking skills such as argumentation and problem solving (Kolstø, 2001; Sadler, 2004), these studies have mostly focused on students' performance in decision-making tasks, such as informal reasoning or argumentation, and less on the cultivation of students' multiple abilities such as cross-domain thinking, the balance of interests, and reflection. Therefore, the present study analyzed the literature on the SSI teaching approach to decision-making to develop learning modules that will help students make rational decisions. Literature Review SSIs involve various conflicting claims and viewpoints, and decision-making refers to an individual's process of collecting, interpreting, weighing, and critiquing data in comparison with various competing alternatives to determine a reasonable choice (Kortland, 1996). Many scholars have proposed different frameworks to describe the decision-making behavior of individuals faced with dilemmas such as SSIs. For example, in 1997, Ratcliffe proposed six decision-making steps: option, criterion, information, evaluation, choice, and reflection. Based on the theory of human infinite rationality, Kortland (1996) proposed a normative model of decision-making, which involves identifying issues, proposing criteria, and interpreting. It further involves evaluating the alternatives, making decisions, acting on the decisions, and monitoring the outcome. Betsch and Haberstroh (2005) proposed a three-phase decision-making architecture, including the preselectional phase, the selectional phase, and the postselectional phase. Lee and Grace (2012) divided SSI-related decision-making into three stages based on the differentiation and consolidation theory proposed by Svenson (1996): identification of issues, differentiation, and consolidation. Fang et al. (2019) reviewed and compared the abovementioned decision-making frameworks. Based on the definitions and descriptions by scholars, they recognized three main components, including formulate the decision-making space, posit a decision-making strategy, and reflect on the decision-making process. This study developed the SSI decision-making learning module based on Fang et al. and Svenson. Thus, it involved three stages: identification of issues, differentiation, and consolidation. Research Method This study used a single-group pretest-posttest design to explore the impact of the proposed module on students' decision-making abilities. Two high school earth-science teachers were invited to develop an SSI decision-making learning module in collaboration with the researchers. The module was taught by one of the teachers and was implemented in the Earth Science elective course in a senior high school for girls in Taipei City. The total number of students evaluated was 172. In the SSI decision-making learning module developed in this study, the issue of coastline change is the decision-making context, and the learning module was developed on a collaborative web-based inquiry science environment (CWISE), an open learning platform modified from the WISE website developed by the University of California, Berkeley. This platform mainly provides an online teaching environment to assist teachers in integrating various learning materials, and it provides teaching scaffolding and even assessment tools. The SSI decision-making learning module developed in this study combines various types of data and presents them in different forms (such as the pre- and post-test, and the worksheets) to guide students in the SSI situation. Based on the research question, two variables were examined: students' decision-making ability while using the learning module and that after using the learning module. The students' decision-making ability while using the learning module was mainly examined based on students' answers to guiding questions in the learning module, whereas the students' decision-making ability after using the learning module was examined using a decision-making ability test based on the three-stage decision-making framework. Results The results of the t test indicate that students' decision-making ability significantly improved in the three decision-making stages after the learning module. Moreover, students' average scores in the posttest were close to the highest score in two dimensions (identification of issues, and consolidation). The results revealed that the learning module designed in this study successfully prompted students to consider issues from multiple perspectives, improved students' use of compensatory methods to measure competitive solutions, and enabled them to accurately assess the quality of their own decisions. The analysis results revealed that students considered at least two aspects to make decisions in the learning module, and most groups could use compensatory methods to make decisions. Although students (15 groups) reported that they favored the use of compensatory methods, they made mistakes while applying them or failed to correctly weigh different aspects of the criteria or, sometimes, confused them with the deletion method. These findings showed that the students did not have a thorough understanding of the compensatory method, indicating that the compensatory method is more cumbersome than the deletion method and may be more difficult to perform and be error-prone for the students. Discussion and Suggestions The study subjects were all female high school students.